The imperatives of technical drawing skills in teaching TVET subjects: the case of Nigeria - Hassanaa, Bashir; Maizam, Alias (International Knowledge Sharing Platform (IISTE), 2017)
This paper focuses on the perceived imperatives of technical drawing knowledge and skills in teaching TVET Subjects. The concept of technical drawing is considered as an important means of communication in engineering, technology, industry and vocational fields. Therefore, the paper discusses the challenges militating against effective teaching and learning of technical drawing in Nigerian institutions. Some of the recommendations proffered are Technical Teachers teaching technical drawing should be given an inductive course in modern methods and techniques of teaching technical drawing to effectively impart the appropriate knowledge and skills of technical drawing to their students. Technical drawing should be made compulsory in all secondary schools in Nigeria. It should be accorded the same status as Mathematics and English, as these subjects form the entry requirements for all science, engineering and technological courses in tertiary institutions in Nigeria and elsewhere in the world. The paper concludes that government should pay closer attention to TVET programmes by putting in place the required infrastructures, facilities and equipment to provide a conducive environment in TVET schools for effective teaching and learning of TVET subjects particularly technical drawing as a key to technological breakthrough.